(untitled) (Journal of actual problems of jurisprudence, 2019)
The legal problems ordered of classifications immovable objects are examined in the scientific article. During research stopped for the certain lacks of civil law, suggestions came into question for the improvement of law on state registrations of rights for the real estate. Keywords: real estate, land, condominium, building.